After summer : a summer boys novel - Abbott, Hailey (New York : Scholastic, 2006)
Summer may be over, but the hook ups are hotter than ever.
Keywords: Teenagers -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Cousins -- Juvenile fiction; Dating (Social customs) -- Fiction; Cousins -- Fiction; Love stories